"A Constant Juggling Act"-The Daily Life Experiences and Well-Being of Doctoral Students - Alison Prendergast; Ruth Usher; Eithne Hunt (MDPI AG, 2023)
(1) Background: There are increasing numbers of doctoral students globally. Poor mental health and well-being among university students, including doctoral students, is a growing concern globally, not least in this post-pandemic era. Engaging in a range of activities every day and maintaining balance between necessary and desired activities is believed to improve health and increase well-being. However, little is currently known about the daily life, activity balance and well-being of doctoral students. This study explored and described the daily life experiences of doctoral students and how pursuing their degree impacted their activity balance and well-being. (2) Method: Purposive sampling methods were used in this qualitative interpretive descriptive study to recruit 10 doctoral students in an Irish university. The data were generated through individual semi-structured interviews and thematically analysed. (3) Findings: Doctoral students have a range of roles, responsibilities and activities that they need to and want to engage in daily. For many, balancing their daily activities and roles alongside their doctoral degree is challenging. Undertaking a doctoral degree can have both a positive and negative impact on well-being. (4) Conclusions: Obtaining an insight into the perspectives and daily life experiences of doctoral students allows for a better understanding of the students' journey. Supporting the well-being of doctoral students is essential to enhance their doctoral education and assist them in successfully completing their degree.